Mattering: Feminism, science, and materialism - Pitts-taylor, Victoria (New York New York university press, 2016)
Feminists today are re-imagining nature, biology, and matter in feminist thought and critically addressing new developments in biology, physics, neuroscience, epigenetics and other scientific disciplines. 'Mattering', edited by noted feminist scholar Victoria Pitts-Taylor, presents contemporary feminist perspectives on the materialist or 'naturalizing' turn in feminist theory, and also represents the newest wave of feminist engagement with science. The volume addresses the relationship between human corporeality and subjectivity, questions and redefines the boundaries of human/non-human and nature/culture, elaborates on the entanglements of matter, knowledge, and practice, and addresses biological materialization as a complex and open process
Keywords: Feminism theory; Feminism and science; Materialism